Differential distribution of N- and O-Glycans and variable expression of sialyl-T antigen on HeLa cells—Revealed by direct fluorescent glycan imaging. (2nd January 2020) - Wu, Zhengliang L; Person, Anthony D; Zou, Yonglong; Burton, Andrew J; Singh, Ravinder; Burroughs, Barbara; Fryxell, Dan; Tatge, Timothy J; Manning, Timothy; Wu, Guoping; Swift, Karl A D; Kalabokis, Vassili
Abstract: Cells are covered with glycans. The expression and distribution of specific glycans on the surface of a cell are important for various cellular functions. Imaging these glycans is essential to aid elucidation of their biological roles. Here, utilizing methods of direct fluorescent glycan imaging, in which fluorescent sialic acids are directly incorporated into substrate glycans via recombinant sialyltranferases, we report the differential distribution of N- and O-glycans and variable expression of sialyl-T antigen on HeLa cells. While the expression of N-glycans tends to be more peripheral at positions where cell–cell interaction occurs, O-glycan expression is more granular but relatively evenly distributed on positive cells. While N-glycans are expressed on all cells, sialyl-T antigen expression exhibits a wide spectrum of variation with some cells being strongly positive and some cells being almost completely negative. The differential distribution of N- and O-glycans on cell surface reflects their distinctive roles in cell biology.